2019
DOI: 10.1182/blood-2019-129125
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reproducibility of the Myoton and Durometer Devices to Measure Skin Stiffness and Hardness in Chronic Cutaneous Graft-Versus-Host Disease Patients

Abstract: INTRODUCTION There is an unmet need for quantitatively measuring skin sclerosis to track the progression of sclerosis in chronic cutaneous graft-versus-host disease (cGVHD). Two candidate technologies are the Myoton, a noninvasive device to assess soft tissue biomechanics, and the durometer, an industrial device measuring surface hardness. Both devices have been shown to have high reproducibility in the context of healthy skin,1 but the reproducibility of these devices in sclerotic cGVHD is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The myotonometer is a promising potential response measure instrument, but many questions must be answered prior to clinical implementation (Table 10). The device has demonstrated high interoperator reliability in measuring stiffness in healthy controls and sclerotic cGVHD patients (Chen et al, 2019;. A recent longitudinal study in sclerotic cGVHD patients showed that stiffness measurements over time correlated with clinically important changes in disease (Baker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The myotonometer is a promising potential response measure instrument, but many questions must be answered prior to clinical implementation (Table 10). The device has demonstrated high interoperator reliability in measuring stiffness in healthy controls and sclerotic cGVHD patients (Chen et al, 2019;. A recent longitudinal study in sclerotic cGVHD patients showed that stiffness measurements over time correlated with clinically important changes in disease (Baker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The device simultaneously extracts five biomechanical parameters, dynamic stiffness, oscillation frequency, relaxation time, creep, and decrement. It has shown high inter-operator reliability to measure dynamic stiffness in healthy controls and sclerotic cGVHD patients (Chen et al, 2019;. While a previous study demonstrated the dynamic stiffness parameter's ability to differentiate sclerotic patients from healthy volunteers, it did not examine other available parameters and lacked post-HCT controls .…”
Section: Introductionmentioning
confidence: 99%
“…S3 (all subjects). Both PD patients (8,9) corresponded to positive outlier slopes (Fig. 1b) in dynamic stiffness (18 N/m/month; 36 N/m/month).…”
Section: To the Editormentioning
confidence: 91%
“…S2). Three patients (patients 1, 2, 7) had PR, two (8,9) had PD, and five (3, 4, 5, 6, 10) had SD. Patient 7 had a reduction in NIH skin score from 3 to 2; no other patients had changes in skin score.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation